Potenciales evocados corticales y evaluación lingüística de pacientes con implante coclear - Reina, Liudis; Torres, Alejandro; Bermejo, Beatriz; Mendosa, Raúl (Revista de Investigación en Logopedia, 2011)
The goal of this study was to examine the usefulness of Cortical Auditory Evoked Potentials (CAEP) as an objective tool that allows us to quantify the process of rehabilitation in patients with cochlear implant. The sample was composed of 20 patients, 12 male and aged between 7 and 16. All cochlear implant users (CI), model Clarion HiRes 90K. All variables showed a statistically significant correlation with the stage of the rehabilitation process in which each patient was. The CAEP reported in patients with CI showed a similar morphology to that obtained in subjects with normal hearing, recording the four components that characterize this response (P1, N1, P2 and N2). It showed a statistically significant correlation between the stages of rehabilitation and the latency of P1 and N1 components. There was also significant correlation between the percentage of incorrect phonemes calculated after applying the Induced Phonological Assessment (IPA) test and latency P1 component. To have objective tools such as the CAEP would guarantee a higher and better use of language rehabilitation, and could help refine rehabilitation techniques for patients with cochlear implants.